DERMATITIS ATOPI FASE INFATIL: SEBUAH LAPORAN KASUS - Helga Pasadena; Andre Hastra (LPPM Universitas Abdurrab, 2023)
Atopic dermatitis (DA) is skin inflammation in the form of recurrent inflammation, accompanied by itching, and affecting certain parts of the body, especially the face in babies (infantile phase) and the flexural parts of the extremities (in childhood phase). Atopic dermatitis often occurs in babies and children, and around 50% disappear by adolescence, sometimes it can persist, or even only start to appear in adulthood. The disorder can occur at any age, and is one of the most common diseases in infants and children, as many as 45% occur in the first 6 months of life. Atopy is a genetically determined condition manifested by a familial predisposition to allergic disorders such as asthma, hay fever, and urticaria. The case of a 6-month-old baby boy has been reported with symptoms of reddish spots accompanied by itching on the left cheek, both groins, and on the left hand. The patient has been given appropriate treatment.